'The debatable territory where geology and archaeology meet': reassessing the early archaeobotanical work of Clement Reid and Arthur Lyell at Roman Silchester. (2nd January 2017) - Lodwick, Lisa A.
Abstract : The first large-scale archaeobotanical study in Britain, conducted from 1899 to 1909 by Clement Reid and Arthur Lyell at Silchester, provided the first evidence for the introduction of Roman plant foods to Britain, yet the findings have thus far remained unverified. This paper presents a reassessment of these archaeobotanical remains, now stored as part of the Silchester Collection in Reading Museum. The documentary evidence for the Silchester study is summarised, before the results are presented for over a 1000 plant remains including an assessment of preservation, identification and modern contamination. The dataset includes both evidence for the presence of nationally rare plant foods, such as medlar, and several archaeophytes. The methodologies and original interpretations of Reid and Lyell's study are reassessed in light of current archaeobotanical knowledge. Spatial and contextual patterns in the distribution of plant foods and ornamental taxa are also explored. Finally, the legacy of the study for the development of archaeobotany in the 20th century is evaluated.